Family history: a vital predictor of cardiovascular health - Kaur, Jaspinder (International Journal of Health, 2014)
Objective: Family history, one of the traditional tools in clinical medicine, is frequently neglected which can be used to identify persons at increased cardiovascular disease (CVD) risk. The present study aimed to determine the influence of family history on cardiovascular health. Methodology: A cross sectional study was conducted on the retired defense personnel to study the relation of socio-demographic variables, physical activity, body mass index, sleep, stress and metabolic syndrome with family history from Jun to Oct, 2013. Chi Square test was used with statistical significance of P value <0.05. Results: A positive family history was reported among 32.77% of the study subjects with statistically significant higher recording by females (60.87%; P <0.01), those who were aged 20-60years (62.60%; P<0.001), and had higher education level (42.61%; P<0.05). A statistically significant stress (29.56%; P<0.001), sedentary lifestyle (72.17%; P<0.05) and insomnia (29.56%) was reported among subjects reporting positive family history. A statistically significant prevalence of metabolic syndrome (36.53%; P<0.05), hypertension (56.52%; P<0.01), obesity (54.78%), dyslipidemia (33.05%; P<0.05) and dysglycemia (31.31%; P<0.05) was more in subjects reporting positive than negative family history (metabolic syndrome: 23.73%; (P<0.05); hypertension: 41.52% (P<0.01); obesity: 50.00%; dyslipidemia: 21.61% (P<0.05); dysglycemia: 21.19% (P<0.05)). Conclusions: A statistical association between positive family history and metabolic syndrome shows CVD susceptibility which prompts to utilize every opportunity to involve concerned families in health education by promoting healthy lifestyle changes in their diet and physical activity. Keywords: Cardiovascular Disease, Family History, Metabolic Syndrome.